Appraising regional anthropogenic heat flux using high spatial resolution NTL and POI data: A case study in the Beijing-Tianjin-Hebei region, China. (1st January 2022) - Wang, Yichen; Hu, Deyong; Yu, Chen; Di, Yufei; Wang, Shasha; Liu, Manqing
Abstract: Rapid urbanization and the aggregation of human activities in cities have resulted in large amounts of anthropogenic heat (AH) emission, which affects urban climate. Quantifying and assessing the AH emission values accurately and analyzing their spatial distribution characteristics is important to understand the energy exchange processes of urban areas. In this study, the high spatial resolution anthropogenic heat flux (AHF) quantification and spatial distribution analysis were conducted using multi-source data in the Beijing-Tianjin-Hebei region (BTH region) of China. First, the AH emission in district and city level were estimated using inventory method based on energy consumption and socio-economic statistical data; Then, AHF spatial quantification models were constructed based on high spatial resolution nighttime light (NTL) data and Point of interests (POI) data, and 130 m × 130 m gridded AHF quantification result in BTH region was realized; Finally, the potential numerical and spatial distribution patterns of AHF were analyzed using various indicators including contribution rate and aggregation index. The results show that: (1) The parameterized index constructed based on NTL and POI data shows a strong correlation with AHF, with R 2 ranging from 0.79 to 0.94 and a mean absolute error (MAE) value of 0.72 w·m −2, which can be applied to the quantification of gridded AHF values with high resolution. The highest total AHF in the study area is 214 w·m −2, and the average value is 2.24 w·m −2 . (2) Considering the sources of AHF, industrial emission sources in BTH region contribute the most to the total AHF, but commercial building emission sources in Beijing have a higher contribution, which can reach 33.8%. (3) Different types of AHF have different spatial aggregation levels. Commercial building emission and human metabolic emission have the highest aggregation level, and transportation emission has the lowest aggregation level. Graphical abstract: Image 1 Highlights: A quantification model for high spatial resolution AHF is applied. AHF spatialized index based on Luojia 1-01 and POI data is developed. Human metabolic and commercial heat emissions are highly spatial aggregated. Industrial is the main source of regional anthropogenic heat emissions.